McClellan's War : The Failure of Moderation in the Struggle for the Union - Rafuse, Ethan Sepp, 1968- (Book collections on Project MUSE., 2005)
This biography of the controversial Union general George B. McClellan examines the influences and political antecedents that shaped his behavior on the battlefield, behavior that so frustrated Lincoln and others in Washington that he was removed from his command soon after the Union loss at Antietam. Rather than take sides in the controversy, Ethan S. Rafuse finds in McClellan's politics and his desire to restore sectional harmony ample explanation for his actions. Rafuse sheds new light on the general who believed in the rule of reason and moderation, who sought a policy of conciliation with the South, and who wanted to manage the North's military resources in a way that would impose rational order on the battlefield.